Educação ambiental em uma perspectiva investigativa: o uso de fotografia autoral na abordagem de impactos ambientais antrópicos - Larangeira Júnior, Benildo Lima (2025)
Environmental issues are a widely discussed topic in the contemporary world, appearing on the agenda of meetings of global leaders and frequently featured in the media and/or digital media. With rapid population growth and increasingly high levels of industrialization and urbanization, the demand for natural resources challenges the development of sustainability practices. Within this context, Environmental Education is a process that enables us to reevaluate how we live and relate to the environment, proposing actions that strive for sustainability. Therefore, this study aims to understand how the use of original photographs can be employed as a pedagogical tool in Environmental Education, promoting an investigative approach to the environmental impacts of anthropogenic origin. To this end, a qualitative approach was used, with methodological assumptions of action research. The research was conducted at a state public school in the city of João Pessoa, Paraíba. The activities targeted three morning classes in the 3rd grade of high school, forming a research universe with a total of 68 students from the Mangabeira neighborhood and surrounding region. The research stages involved the development of an Investigative Teaching Sequence with a presentation of the problem situation and a survey of prior knowledge; a discussion group on environmental impacts; a photography workshop; and the collection, dissemination, and presentation of preliminary and final photographic data, including the creation of an online map. The results include the categorization of students' conceptions of environmental education, with a predominance of the awareness category, which defines a perspective of critical and reflective understanding of anthropogenic environmental impacts. Furthermore, the students explored the concepts, consequences, and possible mitigation measures by collecting and analyzing original photographs of environmental impacts in João Pessoa, Paraíba, using active learning methodologies such as debates, discussion groups, and inquiry-based learning. As promotional material for other students, the students created an online map using the Padlet app, using the photographs they produced and the information they discussed collaboratively in class. Reports on the teaching and data analysis situations were also presented, with pertinent discussions focused on understanding the multidimensional context of anthropogenic environmental impacts in urban environments, using an investigative approach. The conceptual, procedural, and attitudinal learning developed during the teaching situations were also described. At the end of the research, a teaching guide for basic education was made available as an educational resource, including an investigative teaching sequence with guidance on the investigative approach to socio-environmental issues.